2022
DOI: 10.1097/aln.0000000000004116
|View full text |Cite
|
Sign up to set email alerts
|

Anesthesia and Developing Brains: Unanswered Questions and Proposed Paths Forward

Abstract: Anesthetic agents disrupt neurodevelopment in animal models, but evidence in humans is mixed. The morphologic and behavioral changes observed across many species predicted that deficits should be seen in humans, but identifying a phenotype of injury in children has been challenging. It is increasingly clear that in children, a brief or single early anesthetic exposure is not associated with deficits in a range of neurodevelopmental outcomes including broad measures of intelligence. Deficits in other domains in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
40
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 97 publications
(174 reference statements)
0
40
0
2
Order By: Relevance
“…We firmly believe not, because these data are nonhuman and should remain exploratory with the goal of providing translational clues that can guide clinical studies with adequately powered patient cohorts. 3 Therefore, guidelines and regulations on the conduct of safe anesthesia in the very young and beyond should be directed by clinical observations in humans and no other species. E DISCLOSURES Name: Laszlo Vutskits, MD, PhD.…”
Section: See Article P 1203mentioning
confidence: 99%
“…We firmly believe not, because these data are nonhuman and should remain exploratory with the goal of providing translational clues that can guide clinical studies with adequately powered patient cohorts. 3 Therefore, guidelines and regulations on the conduct of safe anesthesia in the very young and beyond should be directed by clinical observations in humans and no other species. E DISCLOSURES Name: Laszlo Vutskits, MD, PhD.…”
Section: See Article P 1203mentioning
confidence: 99%
“…According to the New England Journal of Medicine, February 2017, repeated and prolonged exposure to general anesthesia in infancy and early childhood remains a neurodevelopmental risk factor (Andropoulos and Greene, 2017 ). Although current clinical studies demonstrated that general anesthesia has no significant effect on intellectual development in children, other scientists are calling for further research to assess the long-term effects of anesthetics on neurodevelopment, which is vital for clinical decision-making about surgery and anesthesia in children (McCann and Soriano, 2019 ; Ing et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…With the growing number of infants and children exposed to general anesthesia or sedation for surgery or examinations, the effect of anesthetics on brain development remains controversial. Anesthesia-induced neurotoxicity in the developing brain has been revealed in numerous studies (Vutskits and Xie, 2016 ; Zhou et al, 2021 ; Ing et al, 2022 ), while the neuroprotective property of general anesthetics, especially low-dose anesthetics, is increasingly recognized (Li et al, 2016 ; Wu et al, 2019 ; Zhao et al, 2022 ). As previously described, the application of low-dose ketamine could enhance neurogenesis in mice in the depression model (Deyama and Duman, 2020 ) and showed significant antidepression effects in human studies (Colla et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%